National identity in Indian popular cinema 1947-1987 - Chakravarty, Sumita S. (delhi Oxford university press, 1993)
This book offers the first detailed account of the popular film as it changed during the tumultous decades of Indian nationhood. The study focuses on the cinema's characteristic forms, its range of meanings and pleasures and ideological construction.
Keywords: Sociology